The Prospects of Agricultural and Food Residue Hydrolysates for Sustainable Production of Algal Products - Ehab M. Ammar; Neha Arora; George P. Philippidis (Energies, 2020)
The growing demand of microalgal biomass for biofuels, nutraceuticals, cosmetics, animal feed, and other bioproducts has created a strong interest in developing low-cost sustainable cultivation media and methods. Agricultural and food residues represent low-cost abundant and renewable sources of organic carbon that can be valorized for the cultivation of microalgae, while converting them from an environmental liability to an industrial asset. Biochemical treatment of such residues results in the release of various sugars, primarily glucose, sucrose, fructose, arabinose, and xylose along with other nutrients, such as trace elements. These sugars and nutrients can be metabolized in the absence of light (heterotrophic) or the presence of light (mixotrophic) by a variety of microalgae species for biomass and bioproduct production. The present review provides an up-to-date critical assessment of the prospects of various types of agricultural and food residues to serve as algae feedstocks and the microalgae species that can be grown on such residues under a range of cultivation conditions. Utilization of these feedstocks can create potential industrial applications for sustainable production of microalgal biomass and bioproducts.